Enhancing shear strength of sandy soil using zein biopolymer - Quadri Olakunle Babatunde; Hong Ju Kim; Yong-Hoon Byun (Results in Engineering)
Ecofriendly stabilization using various biopolymers has been explored to enhance the soil strength and the stability of geotechnical structures. This study investigates the improvement of shear strength characteristics in sandy soils treated with a novel protein-based biopolymer, zein. Poorly- and well-graded sands are treated with three different biopolymer contents (1, 2, and 3 %) and cured for 1–28 days. Direct shear tests are conducted under four normal stresses to evaluate the shear behavior and strength parameters of treated and untreated sands. The treated sands exhibit higher peak shear stress and more brittle behavior than the untreated sands due to the formation of biopolymer gel between the soil particles. The treated specimens show a greater improvement in shear strength over longer curing periods, with variation based on soil gradation. After curing for 28 days, apparent cohesion and internal friction angle significantly increase, from 8.1 to 257 kPa and from 26 to 45.4⁰, respectively. Poorly graded sands demonstrate a greater improvement in shear strength compared to well-graded sands, owing to the higher pore spaces available for biopolymer filling and bonding. Thus, incorporating zein biopolymer can significantly enhance the shear strength characteristics of sandy soil, providing a sustainable alternative for soil stabilization in geotechnical engineering.